The Role of Religion and Spirituality in Counseling: Experience of Counsellors in a Collectivist Society - Mohd Radhi Abu Shahim; Melati Sumari; Norsafatul Aznin A. Razak; Kamarul Md Shah; Mazidah Mohd Dagang; Dini Farhana Baharudin (Routledge: Taylor & Francis, 2024)
Indexed by Scopus/ERA